Enduring flows: The transit of drugs in contemporary Honduras - Ziosi, Emilia (Criminology & criminal justice, 2025)
Since the 2000s, Honduras has expanded its role as a transit hub for international cocaine trafficking, with tonnes of cocaine passing through the country every year. Nevertheless, research on illicit drug flows in the country – and more generally across transit areas – remains limited. This resides in a tendency within both academic and institutional discourses to depict illicit flows as detached from societal structures, with little implications for the realities they touch. Drawing on the qualitative analysis of publicly available official US court documents on drug trafficking in Honduras and semi-structured interviews with experts on the country’s drug economy, this article addresses this gap by exploring the movement of US-bound cocaine shipments across Honduras. It explores whether, and how, transient activities such as illicit drug flows become embedded in the territories they traverse. The discussion shows the extent to which the drug trade has become embedded within Honduras’ political and territorial realities, concluding that drugs do not merely pass through transit spaces but become integrated into them. Drug traffickers rely on relationships they establish with both legal and extra-legal actors – including other drug traffickers and state officials – to receive and move drugs across the country. These relationships allow them to obtain access to ‘points of passage’ such as clandestine airstrips, security checkpoints and road networks – all of which are crucial infrastructures for facilitating the transit of drugs. Furthermore, the article reveals both legal and extra-legal actors’ role in exerting control over these logistics infrastructures and therefore in enabling the transnational flow of illicit goods. These insights contribute to broader debates on illicit flows, organised crime and the control of passage points along trade routes, while also shedding light on the often-overlooked role of transit countries like Honduras in the transnational cocaine trade.